Validation of an experimental prototype of thick-layer fixed bed dryer and determination of the quality of the dried soybean grains (Acta Scientiarum. Agronomy, 2018)
The aim of this study was to validate an experimental prototype dryer with a thick-layer fixed bed and determine the quality of the dried soybean grains. The drying system was designed as a chamber with four independent drying cells, with a capacity of 164 kilograms, an air ventilation system and heating with electric heaters. This prototype was used for soybeans with an initial water content of 17% (w.b.). The samples were collected from the top, middle and bottom of the four cells to evaluate the quality of the grains. The experimental design was completely randomized factorial (3 x 4 x 3), with three temperatures settings for the drying air (30, 40, and 50°C), four drying cells and three evaluation positions (upper, middle and lower). The grains did not undergo quality changes as a function of the drying cells. In the upper part of the drying cells, there was a reduction in the specific grain mass (851 kg m-³), an increase in electrical conductivity (140.02 Î¼S cm-1 g-1), reduction in germination (63%) and oil content (7%) compared with the middle and lower dryer positions. The experimental prototype of the fixed bed dryer allowed a uniform distribution of the heated air in the drying cells, which was effective in the drying operation and in maintaining the quality of the soybean grains.